On degenerate diffusion with very strong absorption - Kawohl, Bernhard; Kersner, Robert (Mathematical methods in the applied sciences, 1992)
We prove the existence of weak global solutions to the degenerate diffusion equation (1) with singular absorption term. Moreover we investigate the regularity up to the quenching time and we show by means of explicit solutions that our regularity results are optimal.
Gesehen am 28.06.2023